FINANCIAL PERFORMANCE OF COCOA COMPANIES DURING COVID 19 PANDEMIC: AN ECONOMIC VALUE ADDED (EVA) APPROACH - Eva Yolynda Aviny (Jurnal Agribisnis Indonesia, 2022)
The Covid-19 pandemic brings around a multidimensional crisis that sway the world’s economy and is believed affect the performance of any industry. Therefore this study aims to evaluate the performance of two cocoa processing company before and during Covid-19 pandemic by occupying the financial report of PT Bumi Teknokultura Unggul TBK and PT Wahana Interfood Nusantara frm 2018 till 2020. The result of Economic Value Added (EVA) Analysis confirmed that this pandemic seem affecting the financial performance of the two company, which is both company’s performance tend to decrease, and yet still in good condition since the EVA is positive